How to rationally design homogeneous catalysts for efficient CO2 electroreduction? - Hui Zhang; Qinghua Liang; Ke Xie (iScience, 2024)
Electrified converting CO2 into valuable fuels and chemicals using a homogeneous electrochemical CO2 reduction (CO2ER) approach simplifies the operation, providing a potential option for decoupling energy harvesting and renewable chemical production. These merits benefit the scenarios where decentralization and intermittent power are key factors. This perspective aims to provide an overview of recent progress in homogeneous CO2ER. We introduce firstly the fundamentals chemistry of the homogeneous CO2ER, followed by a summary of the crucial factors and the important criteria broadly employed for evaluating the performance. We then highlight the recent advances in the most widely explored transition-metal coordinate complexes for the C1 and multicarbon (C2+) products from homogeneous CO2ER. Finally, we summarize the remaining challenges and opportunities for developing homogeneous electrocatalysts for efficient CO2ER. This perspective is expected to favor the rational design of efficient homogeneous electrocatalysts for selective CO2ER toward renewable fuels and feedstocks.